U.S. Forward Maritime Strategy and Soviet SSBNs: Optimum Targetting or Escalatory Dilemma - Fanjoy, Richard O. (1990)
As the 1990s approach, there is increasing attention focused on the U.S. force structure required to meet the Soviet strategic threat. Although current events reflect a changing Europe and the viability of the Warsaw Pact is suspect, Soviet strategic forces still constitute a significant threat to our nation. SSBNs in particular, operating from oceanic patrol areas, in port, or from Arctic bastions, provide the Soviets with a capability that is not easily countered. George Lindsey, in his paper "Strategic Stability in the Arctic," argues that NATO SSNs should be used to put pressure on Soviet SSBNs and their Kola Peninsula bases using torpedoes and submarine-launched cruise missiles (SLCMs). He also describes the risk to carrier strike groups operating near Arctic bastions as unacceptable. This paper will address these issues and U.S. strategy options.